Distinct localization of T cell Agrin during antigen presentation - evidence for the expression of Agrin receptor(s) in antigen-presenting cells - Kabouridis, Panagiotis S.; Pimentel, Tatiana A.; Brancaleone, Vincenzo; D'Acquisto, Fulvio; Oliani, Sonia M. [UNESP]; Perretti, Mauro; Jury, Elizabeth C. (Wiley-Blackwell, 2012)
Agrin is over-expressed by activated and autoimmune T cells, and synergizes with the T cell receptor (TCR) to augment cell activation. In the present study, we show that Agrin accumulates to distinct areas of the plasma membrane and that cell activation causes its redistribution. During antigen presentation, Agrin primarily accumulates to the periphery of the mature immunological synapse, mostly in lamellipodia-like protrusions that wrap around the antigen-presenting cell and, conversely, anti-Agrin sera induced a significant redistribution of TCR at the plasma membrane. We also provide evidence for the expression of Agrin receptors in peripheral blood monocytes, dendritic cells and a fraction of B cells. Interestingly, interferon-a treatment, which induces the expression of Agrin in T cells, also augmented Agrin binding to monocytes. Stimulation of monocytes with recombinant Agrin induced the clustering of surface receptors, including major histocompatibility complex class II, activation of intracellular signalling cascades, as well as enhanced dsRNA-induced expression of pro-inflammatory cytokines interleukin-6 and tumour necrosis factor-a. Collectively, these results confirm the location of Agrin at the immunological synapse between T cells and antigen-presenting cells and justify further characterization of its receptors in the immune system.
Keywords: Agrin; Agrin receptor; antigen-presenting cells; immunological synapse; T lymphocytes